THE EFFECT OF FINANCIAL RATIOS ON FINANCIAL DISTRESS IN THE PROPERTY, REAL ESTATE AND BUILDING CONSTRUCTION SECTOR AT THE IDX IN 2019-2023 - Novie Astuti Setianingsih; Wiwiek Kusumaning Asmoro; Atik Tri Andari; Fitria Nur Hamidah; Arvieka Sabilla Putri Setiadi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
The study explores the determinants of financial distress, defined as a company’s incapacity to meet its obligations and considered an early warning of bankruptcy. It specifically analyzes the impact of profitability (ROA), liquidity, leverage, activity, and sales growth ratios on financial distress. The goal is to provide companies, investors, and creditors with a basis for considering these ratios as critical information when assessing a company's susceptibility to financial distress. As a quantitative study, the research sample includes 10 companies from the Property, Real Estate, and Construction Sectors that were part of the LQ45 index on the BEI between 2019 and 2023, selected through the purposive sampling method. The results of the hypothesis testing are as follows: H1, postulating a negative effect of profitability on financial distress, is rejected. H2, postulating a negative effect of liquidity on financial distress, is rejected. H3, which stated that leverage has a positive effect on financial distress, is rejected. Conversely, H4, positing a negative effect of sales growth on financial distress, is accepted. Furthermore, H5, which stated that company size has a negative effect on financial distress, is accepted.